Genetic polymorphisms of IL17A associated with Chagas disease: Results from a meta-analysis in Latin American populations - Strauss, Mariana (2020)
Genetic factors and the immunologic response have been suggested to determine the susceptibility against the infection and the outcome of Chagas disease. In the present study, we analysed three IL17A genetic variants (rs4711998, rs8193036 and rs2275913) regarding the predisposition to Trypanosoma cruzi infection and the development of chronic Chagas cardiomyopathy (CCC) in different Latin American populations. A total of 2,967 individuals from Colombia, Argentina, Bolivia and Brazil, were included in this study. The individuals were classified as seronegative and seropositive for T. cruzi antigens, and this last group were divided into asymptomatic and CCC. For T. cruzi infection susceptibility, the IL17A rs2275913*A showed a significant association in a fixed-effect meta-analysis after a Bonferroni correction (P = 0.016, OR = 1.21, 95%CI = 1.06–1.41). No evidence of association was detected when comparing CCC vs. asymptomatic patients. However, when CCC were compared with seronegative individuals, it showed a nominal association in the meta-analysis (P = 0.040, OR = 1.20, 95%CI = 1.01–1.45). For the IL17A rs4711998 and rs8193036, no association was observed. In conclusion, our results suggest that IL17A rs2275913 plays an important role in the susceptibility to T. cruzi infection and could also be implicated in the development of chronic cardiomyopathy in the studied Latin American population.